A wide angle search for hot jupiters and pre-main sequence binaries in Young Stellar Associations - Oelkers, Ryan J. (2016)
The past two decades have seen a significant advancement in the detection, classification and understanding of exoplanets and binary star systems. The vast majority of these systems consist of stars on the main sequence or on the giant branch, leading to a dearth of knowledge of properties at early times (<50 Myr). Only one transiting planet candidate and a dozen eclipsing binaries are known among pre-main sequence objects, yet these are the systems that can provide the best constraints on stellar and planetary formation models. We have recently completed a photometric survey of 3 young (<50 Myr), nearby (D<150 pc) moving groups with a small-aperture instrument, nicknamed ``AggieCam''. We detected 7 candidate Hot Jupiters and over 200 likely pre-main sequence binaries, which are now being followed up photometrically and spectroscopically.